Factors That Influence Students’ Learning: An Observation on Vocational College Students - Ismail, Mohd Erfy; Hashim, Suhaizal; Abd Samad, Noorazman; Hamzah, Norhasyimah; Masran, Saiful Hadi; Mat Daud, Khairul Azhar; Amin, Nor Fadila; Samsudin, Mohd Ali; Kamarudin, Nurzatulshima (Journal of Technical Education and Training, 2019)
This study examined the factors that influence students’ learning for machine industry courses in Malaysian Southern Region Vocational Colleges. The factors that have been studied were the students’ interest, parental involvement and teachers teaching. This study used the survey design method involving 90 randomly selected 4th year students from three Vocational Colleges as respondents. Primary data were obtained using questionnaires (Cronbach Alpa = .85) and secondary data were based on students’ academic performance test result. The data were analysed with the aid of the Statistical Package for Social Sciences (SPSS) to get the frequency, percentage, mean and standard deviation. The results showed that there was a medium level of influence between students’ achievement and students’ interest, parental involvement and teachers teaching. For student interest factor, students who have good achievement in some subjects were those who have an interest in the subject. In addition, the involvement of parents helping in students’ assignment at home will help them to improve their achievement in school. Next, in the process of teaching, the teacher must inflict the interest of student learning, guiding them in an effective learning way, provide teaching materials and improve their mastery skills. Some suggestions to overcome the challenges identified in this study were also presented at the end of the study.